Agency and Personification: Core Analogical Operators in the Architectural Design Process - Plowright, Philip D (ARCC Conference Repository, 2013)
This paper examines the intrinsic use of the analogical operators of agency and personificationin architectural design. Agency, the capacity of an entity to exert power or force, and personification, the projection of human qualities on non-human entities, exist as examples of a larger set of conceptual tools humans used to interact with their environment. It is common in architectural design to discuss a form or a composition, which is a relationship between forms, as acting on that (agency) or feeling like this (personification). The feeling or activity are part of the transfer of meaning between the designer’s intentions and how another human interprets the design intuitively. The feeling or activity is only projected by the designer onto static forms and does not actually exist in the form or composition – the form is not capable of having human feelings nor does it physically engage in action. What they do is engage cognitive metaphors that are at the heart of human mental processing (Lakoff & Johnson, 1980). By examining agency and personification, the paper will explore major cognitive metaphors and their existence as an inherent part of understanding architecture. The discussion will involve both the theoretical and the practical as well as an introduction to image schema – recurring cognitive structures used to connect patterns with understanding and reasoning. In architectural design, cognitive metaphors will be discussed as part of a toolkit of analogical operators which connect architectural design to architecturalexperience. These operators, it will be seen, use low-level knowledge categories, such as innate and sensorimotor content, to give meaning to architectural objects in context.